Ventajas de la radiografía digital en odontología: una evaluación en contraste con la radiografía convencional en pacientes adolescentes de 14 a 17 años - Arteaga Álvarez, Fredy Patricio (2025)
Introduction: Conventional radiographs, while essential in dentistry, present issues such as cumulative radiation exposure and limitations in image quality, which complicate diagnosis in adolescents. The transition to digital radiography reduces radiation exposure and improves resolution, facilitating early detection of dental problems. Objective: Evaluate the advantages of digital imaging in dentistry compared to conventional radiography, focusing on adolescent patients aged 14 to 17 years. Method: A qualitative approach was adopted through an extensive literature review on digital radiography in dentistry. Relevant information from original and review articles was collected and analyzed, ensuring data validity up to the year 2024. To identify recent studies comparing the advantages of digital radiography with conventional radiography in adolescent patients, scientific sources such as PubMed, Dialnet, and SciELO were used. Results: Digital radiography showed higher diagnostic accuracy in early detection of dental issues in adolescent patients, with superior sensitivity and specificity compared to conventional radiography. Additionally, a notable reduction in radiation exposure, improved image quality, and greater efficiency in the diagnostic process were highlighted, allowing for faster interventions. Conclusions: Digital radiography showed significant advantages over conventional radiography in adolescent patients, offering greater sensitivity and diagnostic accuracy. It also reduced radiation dosage, improving patient safety. The superior image quality facilitated timely diagnoses.